Postprandial lipemia enhances the capacity of large HDL2 particles to mediate free cholesterol efflux via SR-BI and ABCG1 pathways in type IIB hyperlipidemia[S] - Zélie Julia; Emilie Duchene; Natalie Fournier; Natacha Bellanger; M. John Chapman; Wilfried Le Goff; Maryse Guerin (Journal of Lipid Research, 2010)
Lipid and cholesterol metabolism in the postprandial phase is associated with both quantitative and qualitative remodeling of HDL particle subspecies that may influence their anti-atherogenic functions in the reverse cholesterol transport pathway. We evaluated the capacity of whole plasma or isolated HDL particles to mediate cellular free cholesterol (FC) efflux, cholesteryl ester transfer protein (CETP)-mediated cholesteryl ester (CE) transfer, and selective hepatic CE uptake during the postprandial phase in subjects displaying type IIB hyperlipidemia (n = 16). Postprandial, large HDL2 displayed an enhanced capacity to mediate FC efflux via both scavenger receptor class B type I (SR-BI)-dependent (+12%; P < 0.02) and ATP binding cassette transporter G1 (ABCG1)-dependent (+31%; P < 0.008) pathways in in vitro cell systems. In addition, the capacity of whole postprandial plasma (4 h and 8 h postprandially) to mediate cellular FC efflux via the ABCA1-dependent pathway was significantly increased (+19%; P < 0.0003). Concomitantly, postprandial lipemia was associated with elevated endogenous CE transfer rates from HDL2 to apoB lipoproteins and with attenuated capacity (−17%; P < 0.02) of total HDL to deliver CE to hepatic cells. Postprandial lipemia enhanced SR-BI and ABCG1-dependent efflux to large HDL2 particles. However, postprandial lipemia is equally associated with deleterious features by enhancing formation of CE-enriched, triglyceride-rich lipoprotein particles through the action of CETP and by reducing the direct return of HDL-CE to the liver.